2008
DOI: 10.1007/s11999-008-0454-6
|View full text |Cite
|
Sign up to set email alerts
|

Restoration of Femoral Anatomy in TKA With Unisex and Gender-specific Components

Abstract: Recent modifications in total knee prosthesis design theoretically better accommodate the anatomy of the female femur and thereby have the theoretical potential to improve clinical results in TKA by more accurately restoring femoral posterior condylar offset, reducing femoral notching, reducing femoral component flexion, and reducing component overhang. First, we radiographically evaluated whether a contemporary unisex prosthesis would accommodate female anatomy equally as well as male anatomy. Next, we radiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
56
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 15 publications
4
56
0
Order By: Relevance
“…The implications of failing to reproduce the normal asymmetry in PCO are unknown. Clarke and Hentz [6] also found that after TKA, PCO increased by 2.8 mm in men and by 1.3 mm in women and that compromises in sizing were often required with unisex implants, particularly in female patients. Consequently, current prosthesis design and instrumentation do not allow for anatomic reproduction of the PCO of the knee.…”
Section: Discussionmentioning
confidence: 94%
“…The implications of failing to reproduce the normal asymmetry in PCO are unknown. Clarke and Hentz [6] also found that after TKA, PCO increased by 2.8 mm in men and by 1.3 mm in women and that compromises in sizing were often required with unisex implants, particularly in female patients. Consequently, current prosthesis design and instrumentation do not allow for anatomic reproduction of the PCO of the knee.…”
Section: Discussionmentioning
confidence: 94%
“…While there are a few studies assessing clinical outcomes of gender-specific TKA [10,31,32,45], albeit at short followup periods, there are even fewer reports on the results of gender-specific THA [33,46]. This is more of a failure of the surgeons and manufacturers who advocate the need for gender-specific knee designs to conduct large-scale prospective trials to compare these outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Of these 20 reports, there were 15 focusing on the knee and five focusing on the hip (Table 1). There were four reports specifically on clinical outcomes after genderspecific TKA [10,31,32,45] (two of which had a prospective, randomized design [31,32]), and one additional study assessing whether women received benefit from expanded prosthesis sizes [16]. Four studies reported on the effect of gender and modularity on clinical outcomes in THA [25,33,36,46].…”
Section: Methodsmentioning
confidence: 99%
“…It has been demonstrated that women, on average, have smaller distal femurs as well as clinically significant variation in distal femur morphology compared to their male counterparts. One morphological variation in particular is a much larger aspect ratio (anterior/posterior to medial/lateral measurement) which places this patient population at a higher risk for medial/lateral femoral component overhang [35,[37][38][39][40][41] . Different body morphologic types have a significant correlation with distal femoral morphology.…”
Section: Patellofemoral Overstuffingmentioning
confidence: 99%
“…Overhang of ≥ 3 mm in at least one of the predetermined zones of the femoral implant is associated with a 90% increase in the risk of patient-reported knee pain 2 years following TKA [42] . Gender specific femoral components have been demonstrated to minimize femoral overhang and thus post-surgical complications by providing a component that better matches the morphological differences of the female knee [37] . Therefore to minimize complications following TKA, surgeons must be aware of the various morphological differences in the native anatomy of the…”
Section: Patellofemoral Overstuffingmentioning
confidence: 99%